HUBUNGAN LINGKUNGAN FISIK BENGKEL DAN BUDAYA KERJA TERHADAP HASIL BELAJAR PRAKTIK PEMESINAN BUBUT SISWA KELAS XI SMK MUHAMMADIYAH 1 GONDANGREJO - Afrizal Rosyid Fanani; Budi Harjanto; Yuyun Estriyanto (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2021)
This study aims to: (1) Determine the relationship of the physical environment of the workshop on the learning outcomes of lathe machining practices of class IX students in Vocational High School of Muhammadiyah 1 Gondangrejo; (2) Determine the relationship of students' work culture on learning outcomes of lathe machining practices of class IX students in Vocational High School of Muhammadiyah 1 Gondangrejo; and (3) Determine the relationship of the physical environment of the workshop and work culture on the learning outcomes of lathe machining practices of class IX students in Vocational High School of Muhammadiyah 1 Gondangrejo. This research is a quantitative study, with a research method that is ex-post facto. The variables in this study are the physical environment of the workshop and work culture as independent variables and the learning achievement of machining lathe as the dependent variable. The population in this study is class XI students of the Mechanical Engineering expertise program in Vocational High School of Muhammadiyah 1 Gondangrejo with 157 students. The sample in this study is 79 people. Retrieval of data used questionnaire and documentation methods. The data obtained were analyzed by multiple regression analysis. The results of this study are: (1) The physical environment of the workshop has a positive and significant relationship on the learning outcomes of lathe machining practices of class IX students in Vocational High School of Muhammadiyah 1 Gondangrejo with a effective contribution of 16.6% to the high student learning outcomes (2) Work culture has a positive and significant relationship on the learning outcomes of lathe machining practices of class IX students in Vocational High School of Muhammadiyah 1 Gondangrejo with a effective contribution of 18.3% to the high student learning outcomes and (3) The physical environment of workshop and work culture has a positive and significant impact on learning achievement of lathe machining practices the learning outcomes of lathe machining practices of class IX students in Vocational High School of Muhammadiyah 1 Gondangrejo with a effective contribution of 34.9% to the high student learning outcomes.